The Influence of Shopping Experience and Perceived Value Toward Customer Satisfaction and their Impacts on Customer Loyalty at Minimarkets in Aceh - Amri, Saiful; Ma'ruf, Jasman J.; Tabrani, Mirza; Darsono, Nurdasila (International Review of Management and Marketing, 2019)
The aim of this research is to identify: (1) the influence of shopping experience and the perceived value toward customersatisfaction (2) the influence of shopping experience , the perceived value and customersatisfaction toward customer loyalty (3) the indirect influence of shopping experience and perceived value toward customer loyalty at minimarkets in Aceh evaluated through customer satisfaction.The research was conducted at minimarkets in Aceh. The objects of the study are: shopping experience role, and the perceived value between consumer loyalty and customer satisfaction which become the mediating variables. The number of population in this study is all the customers at minimarkets in Aceh, therefore, the sampling technique used in the research was known as the non- probability sampling. It is conducted by taking the purposive sampling method, it means that the population considered as research sample has certain criterias, At the end, there were 270 respondents as the sample population.Structural Equation Modeling (SEM) was the analysis equipment. The study identifies that the shopping experience and perceived value have positive and significant impact on customer satisfaction and shopping experience, moreover, the perceived value and customer satisfaction provide positive and significant impact toward the customer loyalty. In addition, the shopping experience and the perceived value indirectly give positive impact and significantly influence the customer loyalty of minimarkets in Aceh which shown through thee customer satisfaction. Keywords: Shopping experience, perceived value, customer satisfaction and customers loyalty. JEL Classifications: M1, M3 DOI: https://doi.org/10.32479/irmm.7541